2005
DOI: 10.1143/jjap.44.5332
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy and Spectroscopy of Phthalocyanine Molecules on Metal Surfaces

Abstract: We studied the electronic structure of cobalt-phthalocyanine (CoPc) molecules on Au(111) and Cu(100) surfaces by scanning tunneling microscopy and spectroscopy at 5 K. In the differential conductance (dI=dV) spectra, there were some peaks related to the highest occupied molecular orbital (HOMO), the lowest unoccupied MO (LUMO) and the d-orbitals of the Co atom. CoPc molecules on the Cu(100) surface had new electronic states between the peaks related to HOMO and LUMO, while those on the Au(111) surface did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 31 publications
(59 reference statements)
10
40
1
Order By: Relevance
“…Two sharp peaks appearing at ±1.0 V can be attributed to the molecular orbitals. Most previous STM/STS studies of single-decker metal-Pc complexes on metal surfaces have reported similar LUMO and HOMO states at ±(0.9-1.0 V) [8]. For YPc 2 /Au(111), we can consider the two sharp peaks to arise from the LUMO and HOMO states of the upper Pc ligand.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Two sharp peaks appearing at ±1.0 V can be attributed to the molecular orbitals. Most previous STM/STS studies of single-decker metal-Pc complexes on metal surfaces have reported similar LUMO and HOMO states at ±(0.9-1.0 V) [8]. For YPc 2 /Au(111), we can consider the two sharp peaks to arise from the LUMO and HOMO states of the upper Pc ligand.…”
Section: Resultsmentioning
confidence: 68%
“…The development of scanning tunneling microscopy/spectroscopy (STM/STS) allows a full characterization of the surface assembly and electronic structure of such species on a molecular scale. The first STM observation in this field involved adsorption of CuPc on Cu(100), and was followed by explorationsubstrates [4][5][6][7][8][9][10][11][12][13][14][15][16]. Later on, the characterization of the electronic structure of these molecules became an important topic because molecular orbitals can be detected directly by STS.…”
Section: Introductionmentioning
confidence: 99%
“…The bright contrast was explained to be due to the d orbital of the Co atom which contributed to the STM tunneling current [5,6]. Similar investigations have been performed on surface assemblies of MPc (M = Cu, Co, Fe, Pb, Pd, and Mn) on different substrates, and physical properties, such as the Kondo effects in magnetic ion Pc molecules, have been explored [7][8][9][10][11][12][13][14][15][16]. These experiments were mainly performed on thin films on metal/semiconductor substrates in ultrahigh vacuums.…”
Section: Introductionmentioning
confidence: 74%
“…Since organic macromolecules often decompose via thermal evaporation methods, most of the STM results have concerned surface assemblies of Er[(C 12 H 25 O) 8 Pc] 2 [45], Pr(PcOC8) 2 [46], (Nc)Eu(␣-TPPc) [47], and Tb-octa-alkoxylsubstituted Pc double-decker complexes [48] and triple-decker complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[77][78][79][80][81][82][83][84] Although the cross-like shape is similar to the skeleton of the Pc ligand, it is due to hybridization of the molecular orbitals and the electronic state of the Au(111) surface, which contributes more to the image, causing the cross-like shape. [86,87] By examining the symmetry lines connecting the centers of the two diagonal phenyl rings, we can determine the azimuthal rotation of each molecule. One of the two symmetry lines of a molecule is aligned to the close-packed directions of the substrate (A1, A2, or C in Figure 12b), so as to gain larger van der Waals interaction energy due to a larger overlap between the molecule and the substrate.…”
Section: Bonding Configuration Of Pc Moleculementioning
confidence: 99%